2016
DOI: 10.1210/en.2015-2042
|View full text |Cite
|
Sign up to set email alerts
|

Clock Gene Bmal1 Modulates Human Cartilage Gene Expression by Crosstalk With Sirt1

Abstract: The critical regulation of the peripheral circadian gene implicated in osteoarthritis (OA) has been recently recognized; however, the causative role and clinical potential of the peripheral circadian rhythm attributable to such effects remain elusive. The purpose of this study was to elucidate the role of a circadian gene Bmal1 in human cartilage and pathophysiology of osteoarthritis. In our present study, the mRNA and protein levels of circadian rhythm genes, including nicotinamide adenine dinucleotide oxidas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
55
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 43 publications
5
55
0
1
Order By: Relevance
“…Analysis of gene expression patterns in human cartilage revealed that circadian rhythm pathways were among the most disrupted in OA patients (Akagi et al 2017, Soul et al 2018. Several studies have also demonstrated that expression of BMAL1/BMAL1 is significantly reduced in human osteoarthritic cartilage (Dudek et al 2016, Snelling et al 2016, Yang et al 2016a, Akagi et al 2017. Knockdown of BMAL1 in human chondrocytes altered TGF-β signalling and was associated with increased expression of catabolic factors (e.g.…”
Section: Links Between Dysregulation Of Circadian Rhythms and Articulmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of gene expression patterns in human cartilage revealed that circadian rhythm pathways were among the most disrupted in OA patients (Akagi et al 2017, Soul et al 2018. Several studies have also demonstrated that expression of BMAL1/BMAL1 is significantly reduced in human osteoarthritic cartilage (Dudek et al 2016, Snelling et al 2016, Yang et al 2016a, Akagi et al 2017. Knockdown of BMAL1 in human chondrocytes altered TGF-β signalling and was associated with increased expression of catabolic factors (e.g.…”
Section: Links Between Dysregulation Of Circadian Rhythms and Articulmentioning
confidence: 99%
“…Knockdown of BMAL1 in human chondrocytes altered TGF-β signalling and was associated with increased expression of catabolic factors (e.g. MMP1, MMP3, MMP13 and ADAMTS5) (Snelling et al 2016, Yang et al 2016a, Akagi et al 2017, Khurana et al 2019.…”
Section: Links Between Dysregulation Of Circadian Rhythms and Articulmentioning
confidence: 99%
“…We and other groups have already demonstrated that sirtuin-1 (Sirt-1) has a functional role and is a key regulator of many molecules in both catabolic and anabolic pathways in OA chondrocytes [18][19][20][21][22][23]. Sirt-1 has been reported to participate in stress responses by regulating cell death and cellular metabolism through the deacetylation of target proteins in chondrocytes [19,20,22].…”
Section: Introductionmentioning
confidence: 99%
“…Sirt-1 has been reported to participate in stress responses by regulating cell death and cellular metabolism through the deacetylation of target proteins in chondrocytes [19,20,22]. It has also been shown to promote the expression of cartilage-specific genes in chondrocytes [22,24,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation